Inhabiting Suspension: Neoliberalism and the Public Servants in Ismailia's Radio Canal - Ibrahim, Mayar (AUC Knowledge Fountain, 2022)
To be a public servant in 2021 is to endure many sociopolitical and financial hardships as well as many stereotypes. Between living in dire straits and lacking any motive to work, the public servants and their behavior are almost always rendered indolent. Yet, this ambiguous/all-inclusive category needs to be pinned down, shaped in a sociopolitical landscape in which change is analyzed, documented, and conveyed. In the journey of uncovering what it is like to be working in a service governmental institution, Radio Canal in Ismailia allowed me to delve into a segment of the public servant category in a moment of realignment and dismantling of these governmental/service platform. I argue that the people of Radio Canal, as they are witnessing rapid cruel changes and implicit yet recognizable structural violence, are stranded between different eras of state craft. However, some of them are still adhering to the place’s original mandate as a service developmental radio and are actively trying to further postpone its inevitable death. Regarding themselves as media professionals who are also part and parcel of the incumbent regime, the people of Radio Canal are relentlessly trying to hold on to this place as their safe haven that protects them from the uncertainties of neoliberalism.